P-785 Assisted reproduction techniques and the risk of ovarian tumors. (30th June 2022) - Gkamprana, A.M; Adamopoulou, K; Kavvadias, A; Grammatikakis, K; Halkia, E; Patsouras, K
Abstract: Study question: Are fertility treatments associated with increased risk of subsequent development of ovarian tumors? Summary answer: Results from recent studies have been primarily reassuring. However, further investigation is needed to determine whether fertility drug use increases the risk of ovarian tumors. What is known already: In the last decades, the number of fertility treatments is rising worldwide due to postponing childbearing to a later age. The increasing exposure to fertility drugs has brought probable long term sequelae into focus, notably correlation with gynaecological malignancies. Two theories on the association between fertility drugs and ovarian cancer have been proposed, the "incessant ovulation" and the "elevated gonadotropin levels" theory. Use of assisted reproduction techniques (ART) is highly associated with many factors that are known to affect ovarian cancer risk such as parity. Study design, size, duration: Summary of relevant clinical literature and review of all research studies that address the possible relation of assisted reproductive treatments with ovarian tumors. Participants/materials, setting, methods: Published literature in PubMed, Medline and Google Scholar databases from 2011 to 2021 was screened using the following keywords: assisted reproductive techniques, in vitro fertilization, fertility drugs, ovarian cancer, and borderline ovarian tumors. Articles that were written in non- Latin alphabet were excluded for translational reasons. At least two review authors independently evaluated articles for eligibility. Main results and the role of chance: Sixteen cohort and three case-control studies were selected. The majority of included studies reported no increase in ovarian cancer risk among subfertile women treated with ART, compared to either general population or subfertile non-treated women. In eight cohort and one case control studies, the type of fertility drug was clearly reported, including clomiphene citrate, gonadotropins, GnRH (gonadotropin releasing hormone) analogues, alone or in mixed protocols, while in the rest, the type of drug was not specified. Some studies showed a trend for a causative role of increasing dosage or number of IVF (in vitro fertilization) cycles, though statistically insignificant. Based on existing data, genetically vulnerable BRCA mutation carriers should not be excluded from use of ART, although extensive information of the potential association of ovarian stimulating drugs with ovarian tumors should be provided. Data on the association of fertility drug use with borderline ovarian tumors were contradictory. All included studies adjusted or matched for one or more possible confounding factors, such as age, parity and oral contraceptive use. Stratification by cause of infertility, showed an increased risk of ovarian cancer in treated women, with female factor infertility, which was more prominent in case of endometriosis. Limitations, reasons for caution: High clinical and methodological heterogeneity of the included studies, with adjustment for varying confounding factors, relatively short follow–up periods and small samples sizes were noticed. Wider implications of the findings: Ovarian cancer is the deadliest among all gynaecological malignancies. Considering the increasing use of ART worldwide, further clarification of the association between the two is crucial. For this reason larger, prospective studies are needed with sufficient follow-up exceeding 20years so that treated women will reach the ovarian cancer age range. Trial registration number: not applicable